Programmed Cell Death 4 (PDCD4): A Novel Player in Ethanol‐Mediated Suppression of Protein Translation in Primary Cortical Neurons and Developing Cerebral Cortex. (3rd July 2012) - Narasimhan, Madhusudhanan; Rathinam, Marylatha; Riar, Amanjot; Patel, Dhyanesh; Mummidi, Srinivas; Yang, Hsin‐Shen; Colburn, Nancy H.; Henderson, George I.; Mahimainathan, Lenin
<x xml:space="preserve">Abstract</x> Background Prenatal exposure to ethanol (EtOH) elicits a range of neuro‐developmental abnormalities, microcephaly to behavioral deficits. Impaired protein synthesis has been connected to pathogenesis of EtOH‐induced brain damage and abnormal neuron development. However, mechanisms underlying these impairments of protein synthesis are not known. In this study, we illustrate the effects of EtOH on programmed cell death protein 4 (PDCD4), a tumor and translation repressor. Methods Primary cortical neurons (PCNs) were treated with 2.5 and 4 mg/ml EtOH for different time points (4 to 24 hours), and PDCD4 expression was detected by Western blotting. Protein synthesis was determined using [35S] methionine incorporation assay. Methyl cap pull‐down assay was performed to establish the effect of EtOH on association of eukaryotic initiation factor 4A (eIF4A) with capped mRNA. Luciferase assay was performed to determine the in vivo translation. A 2‐day acute 5‐dose binge model with EtOH (4 g/kg body wt, 25% v/v) was performed in Sprague–Dawley rats at 12‐hour intervals and analyzed for PDCD4, eIF4A, and eIF4A–methyl cap association. Results EtOH increased PDCD4 expression in a time‐ and dose‐dependent manner in PCNs, which inhibited the association of eIF4A with methyl cap. EtOH and ectopic PDCD4 expression suppressed in vivo translation in PCNs and RNAi targeting of PDCD4 blocked the inhibitory effect of EtOH on protein synthesis. In utero exposure of pregnant rats to EtOH resulted in a significant increase in PDCD4 in fetal cerebral cortex along with the inhibition of methyl cap–associated eIF4A, compared with isocaloric controls. Increased PDCD4 also occurred in pooled fractions of remaining brain regions. Conclusions Our data, for the first time, illustrate that PDCD4 mediates inhibitory effects of EtOH on protein synthesis in PCNs and developing brain.